Tatars in the History and Culture of Lithuania from the 14th to the 21st Centuries: the Latest Researches - Miškinienė, Galina (Slavistica Vilnensis, 2021)
The Parliament (Seimas) of the Republic of Lithuania the year 2021 declared as the year of the history and culture of Lithuanian Tatars. Lithuanian Tatars have left a bright footprint in the history of Lithuania, and they are a part of its history as well. The descendants of the Tatars of the Grand Duchy of Lithuania live in three countries: Lithuania, Belarus and Poland, and their compatriots – in Crimea, Tatarstan and Turkey.Among the events of the commemorating programme of the Year of the History and Culture of Lithuanian Tatars, which was approved by the Government of the Republic of Lithuania, is the international scientific conference “Tatars in the History and Culture of Lithuania from the 14th to the 21st Centuries: the latest researches”, which took place on the 9th–11th of September 2021 at the Faculty of Philology of Vilnius University live and remotely. International conferences, dedicated to the research of Lithuanian Tatar history, culture, writing and religion, are being organized periodically in Lithuania. As well as at the other conferences, the manuscript heritage (kitabistics) of Lithuanian Tatars – the field of researches, which is being the mostly developed – was discussed at this conference too.
Keywords: Lithuanian Tatars; History; Culture; Vilnius University conferences; Kitabistic